Solid state science and technology XXIX : 29th RCSSST : selected, peer reviewed papers from the 29th Regional Conference of Solid State Science and Technology, November 15-17, 2016, Johor Bahru, Malaysia - Md. Rahim Sahar; Md. Supar Rohani (Diffusion and defect data. Solid state phenomena, 2017)
Collected papers by results of the annual Regional Conference of Solid State Science and Technology (RCSSST) 2016 (Malaysia) offers readers the results of the latest scientific research in the field of solid-state materials and technologies. This book will be useful for many specialists from various fields of applied sciences. Glass, Ceramics, Thin Films, Nanosized Structures, Magnetic Materials, Superconductors, Solid Electrolytes, Polymers, Composites, Micro- and Optoelectronics, Waste Treatment Materials Science.